Math universe: Designing a self-directed learning application for preparing students for mathematical Olympiads - Utami, Anita Dewi; Suwarman, Ramdhan Fazrianto; Rufiana, Intan Sari; Ayufauziah, Nur (Edelweiss Applied Science and Technology, 2024)
The Mathematics Olympiad serves as a competitive platform for students, characterized by its highly challenging problems. However, a significant issue arises due to the limitations faced by both students and their mentors (teachers) in adequately preparing for such competitions. To facilitate self-directed learning and provide access to a diverse range of practice problems, it is imperative to design an educational application that can be accessed anytime and anywhere. This would maximize time efficiency and enhance students’ learning skills in preparation for the Mathematics Olympiad. The proposed application, Math Universe, serves as a medium for students to engage in Self-Directed Learning. Accordingly, the objective of this research is to design Math Universe to effectively and efficiently support students in their preparation for the Mathematics Olympiad. The research employs the Plomp design and development methodology, which includes: 1) Initial investigation phase (situation analysis), 2) Design phase (application design development), 3) Realization phase (application development), and 4) Testing, evaluation, and revision phase (assessment of the developed application’s effectiveness). The findings indicate that the design and functionality of the Math Universe application can be optimized to enhance students’ effectiveness and efficiency in preparing for the Mathematics Olympiad. Trial results demonstrate that intuitive interface design aspects and easy navigation contribute positively to user experience. Furthermore, the content presented is relevant and comprehensible to students from diverse backgrounds, facilitating interaction and understanding of the material.